Physiology of molluscs a collection of selected reviews. Volume 1 - Saleuddin, Saber; Mukai, Spencer (Toronto : Apple Academic Press, 2021)
Physiology of Molluscs: A Collection of Selected Reviews is an informative two-volume sent that brings together some of the most important recent and unique developments in molluscan physiology. Volume One focuses on shell structure, mineralization, the dynamics of calcium transport, shell drilling, byssus proteins, locomotion, and reproduction. With the rapid development of cutting-edge proteomic, molecular biological, and cellular imaging techniques, our understanding of molluscan physiology, specifically in the areas of neurobiology, reproductive biology, and shell formation, has increased exponentially over the last several years. With contributions from some of the world's leading experts in the field of molluscan physiology, this valuable two-volume set fills this void and will serve as an important resource for researchers, professors, and students.
OCLC-licensed vendor bibliographic record.
Keywords: NATURE / Animals; SCIENCE / General; SCIENCE / Life Sciences / Biology / Marine Biology; Mollusks -- Physiology